A CONCEPTUAL FRAMEWORK ON ADJUSTED NET SAVING RATE AS THE INDICATOR FOR MEASURING SUSTAINABLE DEVELOPMENT IN MALAYSIA - Pardi, Faridah; Md. Salleh, Arifin; Nawi, Abdol Samad (Journal of Technology Management and Business, 2015)
The approach to employ gross domestic product (GDP) as the measurement of income for a nation has been in practiced since decades ago. Economists, from various school of thoughts however, have debated for its fallacy of measuring well-being. Maintaining the equal utility levels of consumption and income to be passed onto future generations endlessly is the ultimate goals in economic theory. This idea of constant utility marked the emergence of the term â€˜sustainable developmentâ€™. The initial idea which proposed the basis for sustainability can be traced from the saving and investment rule, where an adequate level of saving should be provided for investment and subsequently reach the optimal economic growth. Optimal rate of economic growth, in further should be enhanced to achieve sustainability by the means of increasing investment and/or replenishing the resources extracted during economic production process. The recently launched New Economic Model under the 10th Malaysian Plan has a continuing objective on sustaining high economic growth. Placing â€˜sustainable developmentâ€™ as the keyword, the term has now become a focus when designing national policies. Economic growth’s framework is now being accompanied with the concept of â€˜sustainable developmentâ€™. Sustainable development means leaving enough capital resources for future generations; or at least equal opportunities as the ones that present generation enjoyed. In this paper, the proposed indicator to measure sustainable development for Malaysia is â€œAdjusted Net Savingâ€ rate. A positive ANS rate is much desired since it would indicate a sustainable path of development progress while negative rate should be avoided as it implies otherwise. This paper aims to present a conceptual framework on ANS rate and discuss its advantages on being a useful tool to measure sustainable development in Malaysia.